PENERAPAN TEKNOLOGI PIROLISIS RECYFUEL UNTUK MENGOLAH SAMPAH PLASTIK LAUT MENJADI ENERGI ALTERNATIF DI DESA PALANG, TUBAN - Joesidawati, Marita Ika; Anggraini, Susanti Dhini; Suwarsih, Suwarsih (Universitas Pattimura, 2025)
Marine plastic waste in Palang Village, Tuban Regency, has caused serious environmental problems, such as water pollution, declining fish catches, and health disturbances due to microplastics. This community service initiative aims to address these issues through the implementation of RECYFUEL pyrolysis technology, which converts plastic waste into alternative energy (diesel) while empowering the Putera Bahari Youth Group. Implementation methods include socialization, technology application training, mentoring and evaluation, and program sustainability measures. The results show an increase in the partners' empowerment level in Management Aspects (100% of partners mastered waste management and financial reporting), Production Aspects (90% of partners were able to independently produce diesel), and Marketing Aspects (90% of partners were able to market diesel products to local fishermen). A total of 50% of plastic waste was successfully processed into diesel, with a conversion rate of 1 kg of plastic yielding 300–400 ml of diesel, along with the creation of a new profitable business opportunity. This program not only reduces environmental pollution but also enhances the economic income of the community. Thus, RECYFUEL technology proves to be an effective and sustainable solution for plastic waste management and the empowerment of coastal communities